1989
DOI: 10.1007/bf00262564
|View full text |Cite
|
Sign up to set email alerts
|

Multiple reconstruction of barley karyotype resulting in complete cytological marking of the chromosome complement

Abstract: A new reconstructed barley karyotype, PK88, which is a quadruple homozygote for three unequal translocations, 1-2, 3-4, 5-7, and one pericentric inversion in chromosome 6, was studied. As a result of these chromosome rearrangements, a complete cytological marking of the complement has been achieved. Due to the specific intra or interchromosomal transfer of particular bands, Giemsa staining of somatic chromosomes provided clear-cut indications about the localization of translocation and inversion breakpoints. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…this approach was successfully applied to map the heterochromatic segments in barley karyotype, since the pericentromeric regions of nearly all chromosomes of this species were found to carry heavy n-bands making it impossible to localize precisely the position of the centromeres directly in Giemsa N-banded plates. As expected, the data concerning the distribution pattern of n-bands along the individual chromosomes, obtained in this study, completely confirmed our results from previous analogous investigations with the parental lines of PK 88-19 (6,8). What is interesting to see on this figure, however, is that the identity of each chromosome of the complement is readily apparent in a routinely stained preparation, thus having no need to use laborious, sophisticated techniques in barley cytogenetic studies.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…this approach was successfully applied to map the heterochromatic segments in barley karyotype, since the pericentromeric regions of nearly all chromosomes of this species were found to carry heavy n-bands making it impossible to localize precisely the position of the centromeres directly in Giemsa N-banded plates. As expected, the data concerning the distribution pattern of n-bands along the individual chromosomes, obtained in this study, completely confirmed our results from previous analogous investigations with the parental lines of PK 88-19 (6,8). What is interesting to see on this figure, however, is that the identity of each chromosome of the complement is readily apparent in a routinely stained preparation, thus having no need to use laborious, sophisticated techniques in barley cytogenetic studies.…”
Section: Resultssupporting
confidence: 90%
“…FISH analysis of the reconstructed chromosomes resulting from this interchange allowed to attain significantly higher precision in the location of the translocation breakpoints compared to our previous studies with the parental lines (6,8). The putative breakpoints of the interchange were found to occur within the regions, 6 mGNs in length, located distally to the GAA hybridization site positioned in the long arm of chromosome 2H at 14 mGNs from the centromere, and at the segment confined within outer borders of the Afa family bands localized terminally in the long arm of chromosome 7H, at positions 49 and 61, respectively ( Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations